Knowledge Of Deafness, Emotional Reactions, And Facilatative Communication Strategies Of Hearing Mothers Of Children Who Are Deaf Or Hard-Of-Hearing: A Comparison Of Experienced Mothers With Those Of Newly To Early Intervention - Che Ahmad, Aznan (2008)
This study investigates the knowledge of deafness, emotional reactions, and communication strategies of hearing mothers of children who are deaf or hard of hearing (D/HH). The study involved sixteen hearing mothers of D/HH children who were allocated into two groups: mothers of D/HH children who had been enrolled in early intervention programme for less than 18 months (New Group) and experienced mothers of D/HH children who had been enrolled in early intervention programme for more than 24 months (Experienced Group)